An Overview of Colorectal Cancer in Tertiary care Cancer Center of Nepal - Magar, Chin Bahadur Pun; Bhatta, Ranjan Raj; Pandey, Greta; Uprety, Suraj; Dhungana, Ishan; Jha, Nandita (Nepalese Journal of Cancer, 2022)
Introduction: Colorectal carcinoma is primary epithelial malignancy arising in the colorectum areas. 98% of colonic and rectum cancers are adenocarcinomas. The prevalence of colorectal cancer has been dramatically growing at an alarming rate globally in recent years. Materials and methods: This is retrospective study at Department of Pathology in B P Koirala Memorial Cancer Hospital effective from 1st January 2018 to 31st December 2019. All the data were retrieved and analyzed. Results:Total 56 colorectal cancer cases were analyzed, among them 36 cases were males accounting 64 % and 20 cases were females accounting 36 %. Rectum was the commonest site and commonest age group was 61-70 years accounting 55.3%. 44.6% cases were in advanced stage either stage III or IV. Conclusion:Colorectal cancer is more common in males than in females. Most commonly affected age group was 61-70 years. Most common histological type was well differentiated adenocarcinoma. 44.6% cases were diagnosed in advanced stage either stage III or IV.